Management of Coexisting Luteal and Follicular Ovarian Cysts in a Holstein Friesian Crossbred Cow - Lavanya, Maharajan; Praveen, Selladurai; Abhijeet, Sakhare; Harshit, Saroha; Gowdar Veerap pa, Vedamurthy; Jeyakumar, Sakthivel (The Indian Journal of Animal Reproduction, 2025)
Ovarian cysts are one of the most common postpartum ovarian dysfunctions in cattle. The present case reports an  incidence of COD and its successful therapeutic management in a cow at institute dairy herd. Per-rectal examination of  the genitalia and transvaginal ultrasound examination of the ovaries at ten days interval confirmed the persistence of a  hypoechoic structure (4.05 cm in diameter) as a luteal cyst. Treatment with CIDR+Ovsynch protocol with timed AI was  effective in the induction of estrus and resulted in successful establishment of pregnancy.
Keywords: Cattle; Follicular cyst; Luteal cyst; Ovarian cysts; PGF2α